2016
DOI: 10.1002/glia.23038
|View full text |Cite
|
Sign up to set email alerts
|

Conditional rod photoreceptor ablation reveals Sall1 as a microglial marker and regulator of microglial morphology in the retina

Abstract: Neurodegeneration has been shown to induce microglial activation and the infiltration of monocyte-derived macrophages into the CNS, resulting in the coexistence of these two populations within the same lesion, though their distinct features remain elusive. To investigate the impact of rod photoreceptor degeneration on microglial activation, we generated a toxin-mediated genetic model of rod degeneration. Rod injury induced microglial proliferation and migration toward the photoreceptors. Bone marrow transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 54 publications
(88 reference statements)
4
34
1
Order By: Relevance
“…Of these three modules, however, only module 18 was enriched (FDR <0.01) for genes down-regulated by PLX3397 (Supplementary Figure 9), suggesting a selective effect on module 18 expression by PLX3397 as opposed to a global down-regulation of microglial modules due to gross microglial depletion. Consistent with this interpretation, we observed that the expression of the microglia-specific gene Sall1 35 was up-regulated by PLX3397 (Log 2 fold change = 0.17, FDR = 2.16x10 −6 ).…”
Section: Resultssupporting
confidence: 81%
“…Of these three modules, however, only module 18 was enriched (FDR <0.01) for genes down-regulated by PLX3397 (Supplementary Figure 9), suggesting a selective effect on module 18 expression by PLX3397 as opposed to a global down-regulation of microglial modules due to gross microglial depletion. Consistent with this interpretation, we observed that the expression of the microglia-specific gene Sall1 35 was up-regulated by PLX3397 (Log 2 fold change = 0.17, FDR = 2.16x10 −6 ).…”
Section: Resultssupporting
confidence: 81%
“…Early microglia, like EMPs, express genes associated with cell cycle signaling pathways and the TF E2f6 and DNA methyltransferase-1 (Dnmt1), which may help them populate the brain. The genes expressed by premicroglia, including the TFs early growth response-1 (Egr1) and spalt-like TF-1 (Sall1), are associated with neural maturation and synaptic pruning (29,30). Later, as the brain …”
Section: Transcriptional Control Of Microglia Identitymentioning
confidence: 99%
“…Human and mouse microglia uniquely and highly express SALL1 as compared with other macrophage populations, suggesting that it functions as an LDTF (34,35,37). Sall1-deficient animals have normal microglia colonization in the brain, but the microglia exhibit an abnormal ameboid morphology (30). Moreover, in the absence of Sall1, …”
Section: Ldtfs That Establish Physiological Microgliamentioning
confidence: 99%
“…In fact, most recent in situ analyses of ramified and reactive retinal microglia rely on Iba1 staining [26][27][28][29][30] as the marker allows consistent and reliable staining of microglia somata and their processes in a broad spectrum of different activation phenotypes [31][32][33] . In general, a combined in situ analysis of retinal microglia using sections and flat mounts as presented in our protocol is recommended.…”
Section: Development Of the Protocolmentioning
confidence: 99%